p-Cymene metallo-derivatives: An overview on anticancer activity - Hassan, Shardar Mohammad Hafiz; Ray, Pranta; Hossain, Rajib; Islam, Muhammad Torequl; Salehi, Bahare; Martins, Natália; Sharifi-Rad, Javad; Amarowicz, Ryszard (Cellular and Molecular Biology, 2020)
Metallo-drugs have gained a huge attention among scientific community in the couple years. These drugs types have become important compounds in cancer therapy, where, for instance, platinum complexes are being used against many tumors worldwide. Nonetheless, to p-cymene metallo-derivatives a promising anticancer potential has also been increasingly proposed. In this sense, the present review aims to provide an in-depth revision of p-cymene metallo-drugs possible mechanisms of anticancer action for upcoming pharmaceutical and biotechnological prospects. p-cymene metallo-derivatives have revealed very interesting anticancer activities in various test systems, including cancer cells, being thus worth of note to deepen knowledge through clinical trials on their upcoming use for cancer chemotherapy combination.